Department of Human Services reconciliation plan 2002-2003. - South Australia. Department of Human Services (Adelaide : Dept. of Human Services, 2002)
A plan that identifies six critical outcomes to be achieved by the Department of Human Services for Aboriginal people living in South Australia; quality of life; respect for cultural diversity; workforce capacity; participation and building community capacity; portfolio performance and accountability; details the environmental context, performance indicators, and reconciliation activities for each outcome area.
Keywords: South Australia. -- Department of Human Services; Aboriginal Australians -- Services for -- South Australia; Aboriginal Australians -- Government policy -- South Australia; Aboriginal Australians -- South Australia -- Government relations; Aboriginal Australians -- South Australia -- Social conditions; Health services; Race relations - Reconciliation; Government policy - State and territory - South Australia; Community development; Social welfare; South Australia -- Race relations; South Australia (SA)